Recurrent Hypoglycemia in a Case of Congenital Analbuminemia - Martin Litzel; Gianluca Caridi; Francesca Lugani; Monica Campagnoli; Lorenzo Minchiotti; Stefan Fischli (Case Reports in Endocrinology)
In congenital analbuminemia (CAA), mutations in the albumin gene result in a severe deficiency or absence of plasma albumin. Only about 90 cases have been reported to date, but the specific features of glucose and lipid metabolism in congenital analbuminemia have only been studied in a rat model of analbuminemia. We report the case of a female patient hospitalized for a streptococcal skin infection who showed recurrent hypoglycemia. A diagnosis of CAA was confirmed by mutation analysis and by the detection of a single base variation in the ALB gene. Hypoglycemia was first documented after a fasting period during acute illness. Recurrent hypoglycemia persisted despite good general condition and normal nutrition during antimicrobial therapy with moxifloxacin. Several contributing factors causing this hypoglycemia can be discussed. Individuals with CAA are prone to adverse drug effects caused by changes in drug-protein binding properties. It is unclear if specific changes of glucose and lipid metabolism in CAA constitute a risk factor for hypoglycemia.